ASSESSMENT OF MICROBIOLOGICAL QUALITY AND ASSOCIATED HEALTH RISKS OF RAW MILK SOLD IN AND AROUND HYDERABAD CITY - B.SRINU; A.VIJAYA KUMAR; M.SHASHI KUMAR; B.V.L NARAYANA; T.MADHAVA RAO (International Journal of Pharma and Bio Sciences, 2012)
The present study was done to assess the microbiological quality and related health risks of raw milk sold in and around Hyderabad city. A total of 60 milk samples were collected from milk sellers on bicycle (15) and two wheelers (15), local dairy farms (10), small hotels (10) and tea stalls (10) in and around Hyderabad city from January to March, 2012. Quality and milk borne hazards were assessed with combination of tests to quantify the total bacteria, the pathogenic microbes such as Escherichia coli, Salmonella and Staphylococcus and the occurrence of brucellosis (Abortus bang ring test). Plate count agar for total bacterial count and specific media for the pathogenic microbes were used in the study. The average total bacterial count in all the samples was recorded as 162 colonies at 106 dilutions. 27, 21 and 33 samples gave positive results out of 60 samples for Escherichia coli, Salmonella and Staphylococcus respectively with mean count ranged from 103 to 104 CFU/ml. Out of 60 samples 15 samples (25%) were positive for brucellosis.